Applied Geographical Information System (GIS): Overlay analysis - Madzimure, Farai (Pure and Applied Science Advances, 2017)
Technological limitations have posed challenges in integrating wildlife conservation needs with human land uses and other infrastructural development needs. The advent of the Global Position System (GPS) technology has made it possible to collect elephant location and human land use data. Geographic Information System (GIS) software has allowed overlay analysis of elephant location data and human land uses. This study, therefore demonstrates how the overlay analysis function in GIS can be employed to link human land use data layers and elephant location. To achieve this, the overlay analysis function was used to combine elephant location data with distance maps of each human land use factor. The distance values for each human land use factor were extracted at each elephant location using the map value function in ILWIS. The resultant table show extracted elephant location values and corresponding distances values for each human land use factor. Further research can be conducted by exporting elephant location values and corresponding land use values to SPSS to predict the human land uses which significantly influence the presence or absence of elephants. This study also recommends the use of the overlay analysis tool in Environmental Impact Assessment projects to model the most suitable site for a proposed project such as dam construction.